A Study of the graduates of five agricultural high schools in Luzon - Logan, Felix B. 1910- ([Quezon City s.n.], 1958)
The concerns of this study are the socio-economic and occupational status of 1946-1952 graduates- their employment, income, wages and attitudes- in order to know whether Agricultural High Schools can bring "more capable human resources" to the farm or whether their graduates are the same in disposition with any other secondary schools. Any information on the matter may change the attitude of our lawmakers and policy determiners in their policies about these vocational schools. It may modify the concensus that many graduates of Agricultural High Schools do not make use of their training.
Bibliography: l. 150-158.
Thesis (M.Ed.)--University of the Philippines, 1958
Typescript (carbon copy)
Vita
Keywords: Agricultural education -- Luzon